Inventory dynamics and soil factors affecting soil-to-plant ¹³⁷Cs transfers in Fukushima forest ecosystems - Zhang, Jian, author; Johnson, Thomas, advisor; Brandl, Alexander, committee member; Sudowe, Ralf, committee member; Pilon-Smits, Elizabeth, committee member (Colorado State University. Libraries, 2020)
The objective of this study was to understand the soil factors affecting soil-to-plant transfer factors in understory plant species as well as their contribution to the total 137Cs inventory in aboveground biomass within the Fukushima forest ecosystem. Radiocesium contamination from the March 2011 accident at the Fukushima Da-ichi Nuclear Power Station (FDNPS) was initially deposited on the forest canopies with deposition into the soil occurring over the next few years through litterfall and precipitation. Measurements taken from the Yamakiya site in 2014 show that the contribution of understory plants to the total inventory of radiocesium in aboveground biomass was very low compared to the dominant Japanese cedar trees. However, measurements were not taken in other affected sites within Fukushima prefecture as well as potential change in concentrations of radiocesium in understory biomass since 2014. Data for evaluating the transfer factors was obtained through sampling of soil and understory plants at the Yamakiya, Tsushima, Tomioka, Okuma, and Yokomuki sites inside Fukushima Prefecture. Both 134Cs and 137Cs measurements were collected, however 134Cs concentrations were negligible compared to 137Cs so only 137Cs data was considered. 137Cs content was determined using gamma spectroscopy of the soil and plant samples and to find the concentration of bioavailable 137Cs within the root profile of the understory plants as well as 137Cs concentration within the understory plant itself. The soil and plant 137Cs concentration was used to determine the soil-to-plant uptake factors for the sampled understory species as well as the contribution of the understory plants to the total 137Cs inventory in aboveground biomass. The effect of soil exchangeable [K+], exchangeable [Cs+], exchangeable 137Cs activity concentration, total 137Cs activity concentration, and pH on 137Cs uptake by understory plants was determined through the soil-to-plant uptake factors at the various sample sites. The same data was used to find the 137Cs deposition in the soil, 137Cs inventory in Yamakiya, and patterns between plant activity concentration between plant species. Soil measurements showed a logarithmic decrease in 137Cs activity concentration with decreasing soil depth. Measurements also supported a 4.39 year effective half-life using GIS and Nuclear Regulatory Authority data, however using IER data a radiological half-life of 30.17 years was supported instead. The majority of 137Cs inventory in Yamakiya was found to be in soil (80.54%) and trees (18.52%) with understory plants making up a negligible contribution. This contribution by trees was much higher than the one found in previous years. For understory plants, it was found that there are higher 137Cs activity concentrations in the more metabolically active portions of the plants. 137Cs was a significant contributing factor across all understory plant species in predicting the soil to plant transfer factors. The ability to properly estimate the activity concentration of understory plants using only the one soil factor can contribute to faster estimation of potential 137Cs concentrations in plants or uptakes by herbivores in areas contaminated by 137Cs. The further understanding of 137Cs dynamics in forest ecosystems will assist in creation of a long-term forest radiation contamination management strategy.
Keywords: forest; radiation; soil; Fukushima; cesium; radioecology